Adaptive and Innovative Behavior of Public Relations Officers During the COVID-19 Crisis: Formulating the 5C Model - Vardiansyah, Dani; Delliana, Santi; Evelina, Lidya Wati; Febriani, Erna (Scriptura, 2025)
The Covid-19 pandemic disrupted the operational stability of businesses across sectors, forcing Public Relations Officers (PROs) to adapt and innovate rapidly to sustain organizational resilience. This study investigates PRO behavior within organizations ranging from micro, small, and medium enterprises (MSMEs) to national-level institutions, focusing on how communication practitioners navigated crisis-induced uncertainty. Informants were purposively selected PROs who directly managed organizational communication during the pandemic, and data were gathered through in-depth interviews conducted between 2021 and 2022. The urgency of this study lies in the limited empirical documentation of PRO behavioral patterns across organizational scales during COVID-19, despite the pandemic serving as a stress test for crisis communication capacity. Using a postpositivist paradigm and qualitative case study approach, this research employed the Kübler-Ross Change Curve as an analytical indicator to map adaptive and innovative responses. Findings reveal seven behavioral phases: shock, denial, frustration, depression, experiment, innovation decision, and integration; supported by five strategic endeavors: alignment building, communication enhancement, motivation ignition, capability development, and knowledge sharing. The study offers conceptual novelty through the proposed 5C Formula for Adaptation and Innovation, in which changing the paradigm and creating new habits represent adaptive stages. At the same time, creative approaches, channel optimization, and collaborative agreements constitute the innovation stages. This formula contributes an integrative framework for understanding PRO crisis behavior and offers practical guidance for future organizational communication strategies in prolonged disruptive conditions.